Reabilitação empresarial: por um novo paradigma no tratamento do devedor falido no Brasil - Beltramini, Danieli Carla Cardozo (2024)
This dissertation analyzes the obstacles to the rehabilitation of bankrupt businesspeople in Brazil and proposes solutions to overcome them. The Brazilian bankruptcy system, despite the advances brought by Law 11.101/2005 and the reform of Law 14.112/2020, still lacks effective mechanisms to provide honest entrepreneurs with a second chance. Through bibliographical research, documentary analysis and comparative study, four main barriers were identified: i) the indiscriminate application of the minor theory of disregarding legal personality; ii) the non-extinction of tax obligations; iii) procedural slowness; and iv) the absence of specific treatment according to the economic size of the debtor. The work examines the historical evolution of bankruptcy law, analyzes the interpretation of norms considering constitutional principles and proposes legislative reforms to implement an effective fresh start model. It is concluded that there is a need to reinterpret current regulations and issue a specific regulatory framework for micro and small companies, establishing simplified procedures and objective criteria to distinguish fraudulent and non-fraudulent bankruptcies. The proposals presented aim to balance the protection of creditors with the need to provide a second chance to the debtor in good faith, contributing to the economic and social development of the country.